The Influence of Educational-Themed Films on the Learning Motivation of University Students - Nucke Yulandari; Sri Indah; Nurul Ramadhani; Romi Yanti; Riska Mahya (Jurnal Psikologi Terapan, 2025)
Learning motivation plays a vital role in achieving optimal learning outcomes. This study aimed to examine the effect of educational-themed films on enhancing students’ learning motivation. The research involved 14 psychology students from Malikussaleh University who were divided into an experimental group and a control group. The research design used was a pretest-posttest control group design. The experimental group was given an intervention using Nussa and Rara video media, while the control group was not. The results showed that the mean score of the experimental group (10.60) was higher than that of the control group (9.30). The significance value obtained was 0.015 (p < 0.05), indicating a significant difference in the gain scores between the two groups. These findings suggest that educational-themed films have a positive effect on increasing students’ learning motivation and can be used as an alternative media in the learning process to enhance motivation and engagement.